Neighbourhood Ethnic Diversity, Child Health Outcomes and Women's Empowerment. Issue 9 (2nd September 2019) - Dinku, Yonatan; Fielding, David; Genç, Murat
Abstract: Much of the existing literature suggests that ethnic diversity undermines economic development. However, there are also ways in which local ethnic diversity might be beneficial, and we show that in the case of Ethiopian child health, the benefits of diversity can outweigh the costs. We find that children in relatively diverse communities are better nourished and more likely to receive a full set of vaccinations. There is some evidence that one explanation for this effect is that women in relatively diverse communities are better informed about health issues and more empowered in making healthcare decisions.